Optimizing Health Service Efficiency Through Public Satisfaction and Waiting Time Analysis at Public Health Center - Sri Syaida Ariska; Jammin, Maria Inge; Fertitura, Yulinda (LPPM Universitas Jambi, 2025)
Background: Public health centers are integral to providing accessible healthcare services, particularly in local communities. Ensuring public satisfaction with these services is critical to building trust and improving service delivery. This study aims to assess public satisfaction with registration counter services at the Public Health Center, identify key challenges, and propose solutions to enhance service quality. Method: This study aims to utilize a quantitative approach by collecting primary data through structured questionnaires administered to patients visiting the General Clinic and registration counter in December 2024. Secondary data were obtained from previous satisfaction reports and integrated health center records. The data were analyzed using a Likert scale to measure satisfaction levels and identify key problem areas. Result: The overall public satisfaction index was calculated at 80.46%, categorized as good. However, several challenges were identified, particularly regarding long waiting times at the registration counter and difficulties in using the newly implemented online registration system. The lowest satisfaction scores were recorded for “Access to Online Services” (76.33%) and “Service Time” (76.06%). Contributing factors included limited staff availability during peak hours, insufficient training for both staff and patients on the online system, and inadequate physical infrastructure, such as overcrowded waiting areas and insufficient seating. Conclusion: Addressing operational inefficiencies and optimizing online registration systems can significantly improve public satisfaction. Recommendations include increasing staff availability, providing training on the online system, and enhancing physical infrastructure. Regular evaluations and continuous improvements are necessary to maintain high-quality service delivery.